2012
DOI: 10.3758/s13423-012-0324-9
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of strategy use in the Iowa gambling task: A comparison of win-stay/lose-shift and reinforcement learning models

Abstract: The Iowa gambling task (IGT) has been used in numerous studies, often to examine decision-making performance in different clinical populations. Reinforcement learning (RL) models such as the expectancy valence (EV) model have often been used to characterize choice behavior in this work, and accordingly, parameter differences from these models have been used to examine differences in decision-making processes between different populations. These RL models assume a strategy whereby participants incrementally upd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(132 citation statements)
references
References 27 publications
6
121
2
1
Order By: Relevance
“…Choice-history biases have been observed when subjects had to make judgments about physical weights (9), auditory stimuli (12,16,18), or visual stimuli (4,8,10,11,14,18). As in our experiment, subjects show a diversity of biases ranging from switching strategies (4,9,12,14,16), to staying strategies (10,11,18), to success-stay/fail-switch strategies (5, 6, 8, 18).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Choice-history biases have been observed when subjects had to make judgments about physical weights (9), auditory stimuli (12,16,18), or visual stimuli (4,8,10,11,14,18). As in our experiment, subjects show a diversity of biases ranging from switching strategies (4,9,12,14,16), to staying strategies (10,11,18), to success-stay/fail-switch strategies (5, 6, 8, 18).…”
Section: Discussionmentioning
confidence: 83%
“…These biases generally manifest as switch-after-failure A B or as stay-after-success strategies (8,10,11,18). Both types of biases were disadvantageous in that they reduced sensitivity for most of the subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most studies of IGT have concentrated on its ability to distinguish between healthy and clinical populations, recent studies have focused on the variability in decision performance found among healthy participants (Steingroever et al, 2013;Worthy et al, 2012). Steingroever et al conducted a meta-analysis to determine if healthy participants consistently (1) select good decks to a greater extent than bad decks, and (2) go through a clear explo- Figure 2.7: Screen shot of the original Iowa Gambling Task by Bechara et al (2005).…”
Section: Materials and Methods Of The Original Igtmentioning
confidence: 99%
“…Most IGT studies that explicitly provide such information (e.g., Bechara et al, 1999;Lehto & Elorinne, 2003;Worthy, Hawthorne, & Otto, 2013) identify a significant sub-group of healthy control participants (e.g., 23% of controls in Bechara et al, 1999;7.5% in Lehto & Elorinne, 2003) who exhibit impaired performance in the IGT, often similar and sometimes even worse than the performance of the patients (e.g., Bechara et al, 1999;Lehto & Elorinne, 2003). Although the behavior of these healthy underperformers resembled that of the patients, they differed in terms of the physiological results (i.e., SCR), which reflect emotional reactions.…”
Section: Summary and Comparison With Clinical Researchmentioning
confidence: 99%